Estudo da sensibilização de cães com dermatite atópica na região central do Rio Grande do Sul - Pereira, Desydere Trindade (2015)
Canine atopic dermatitis (CAD) is a common dermatosis, defined as a genetic-based disease, which predisposes to cutaneous inflammation and pruritus, mediated by class IgE immunoglobulins directed against specific antigens in most cases. Clinical diagnosis may be later complemented by skin allergic and/or serological tests (ELISA). The aim of these tests is to identify possible allergens in order to enable the clinicians to select candidate antigens for allergen specific immunotherapy. This work aimed to identify the sensitization profile of 58 dogs with atopic dermatitis diagnosis. All animals were submitted to intradermic test (IDT) and screened for the presence of antibodies against different allergens using a serologic test. House dust mites are described as the most frequent allergens in all continents. However, the positivity to C. dactylon is not commonly described and may be characteristic for the region. With this work it was possible to identify the main allergens involved in the immunologic response of atopic dogs residing in Rio Grande do Sul, pointing to the importance to include C. dactylon in screening tests for allergy.